A cross-sectional observational study of birefringent particulates in bronchoalveolar lavage cytology in horses with equine asthma from the West v East coasts of the USA. - Melissa R Mazan; Edward F Deveney (PLoS ONE, 2024)
Equine asthma (EA) is an important cause of wastage in the USA horse industry. Exposure to organic particulates, from stable dust, airborne pollen, and fungal loads, is posited to be the main cause. Dust arising from the earth's crust has been largely ignored as a contributor to EA in the veterinary literature. The objectives of this study were to investigate the occurrence of birefringent particulates in the bronchoalveolar lavage fluid (BALF) of horses with a clinical complaint of EA residing in the arid West of the USA v. the East, in an effort to determine the contribution of geolocation to geogenic dust exposure. We analyzed BALF cytology and historical data sent to our referral clinical laboratory from 148 horses from the West Coast and 233 horses from the East Coast of the USA over a 6-year period, using light microscopy to determine cell proportions and other visible elements as well as a polarizing lens to detect birefringent material. Univariate analysis showed that horses from the West coast were significantly more likely to have birefringent particulates in the BALF than horses from the East coast (40.5% v. 8.6%, p < 0.001); while horses from the East had higher BALF neutrophil proportions. Horses from the West also had lower proportions of neutrophils in the BALF than those from the East (27.1 v. 10.9, p < .001). Using historical and BAL data in a forward stepwise binary logistic regression model with presence of birefringent particulates found within alveolar macrophages as the outcome, geographical location in the West retained significance as a predictor (OR 8.0, CI [4.3-14.8], p< .001). While the birefringent particulates cannot be identified on the basis of polarizing microscopy alone, this study provides evidence that horses from the West are exposed to inorganic particulates that may contribute to signs of equine asthma.